MRI changes and expressions of neuron-specific enolase and monocyte chemoattractant protein-1 in cerebrospinal fluid in patients with severe herpes simplex virus encephalitis: Expressions of NSE and MCP-1 in cerebrospinal fluid - Yao, Yan; Gu, Juxian; Li, Meng; Li, Guoce; Zhao, Li; Ai, Jingyi (Cellular and Molecular Biology, 2022)
The objective of this research was to analyze the MRI changes and the expression of neuron-specific enolase (NSE) and monocyte chemoattractant protein-1 (MCP-1) in cerebrospinal fluid (CSF) of patients with severe herpes simplex encephalitis. For this purpose, 68 patients with severe herpes simplex virus encephalitis diagnosed and treated in our hospital from April 2020 to April 2021 were selected as the study objects of the study group. In addition, 68 healthy people who underwent normal physical examinations in our hospital were selected as the control group at the same time. They were examined by magnetic resonance imaging (MRI) within one week after the study group was enrolled. CSF samples were collected one week after the onset of the disease in the study group and 2-4 days after the first spinal anesthesia in the control group, Enzyme linked immunosorbent assay (ELIEA) was used to detect the expression of NSE and MCP-1 in cerebrospinal fluid of the two groups, and the linear correlation between NSE and MCP-1 were analyzed. Results showed that compared with the control group, the expression of NSE and MCP-1 in the cerebrospinal fluid of the study group increased significantly (P<0.05). The expression of NSE and MCP-1 in patients with severe herpes simplex encephalitis in a coma was significantly higher than that in patients without severe herpes simplex encephalitis in a coma (P<0.05). NSE and MCP-1 were positively correlated (r=0.597, P=0.001). NSE and MCP-1 were risk factors for severe herpes simplex encephalitis, and the difference was statistically significant (P<0.05). In conclusion, magnetic resonance imaging of patients with severe herpes simplex encephalitis is characterized by multiple lesions in the temporal lobe, insula, and frontal lobe base (especially the marginal system involved) with unilateral or bilateral asymmetric distribution, and abnormal high expression of NSE and MCP-1 in the cerebrospinal fluid of such patients, which has important value in the early diagnosis of this disease.